2016
DOI: 10.1159/000456031
|View full text |Cite
|
Sign up to set email alerts
|

Luminex LiquiChip System for the Evaluation of Cytokine Levels in Patients with Contact Dermatitis to Potassium Dichromate

Abstract: Background: Allergic contact dermatitis (ACD) is associated with increased production of cytokines. The patch test is the “gold-standard” diagnostic method, but it poses a risk of false results. Objective: To evaluate a novel laboratory technique, the Luminex LiquiChip, which simultaneously measures blood levels of multiple cytokines, as a diagnostic tool in patients with chrome-induced ACD. Methods: The study group included 20 patients with ACD and relevant patch test results for potassium dichromate and 19 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…In 2013, Martins and Reis reported on in vitro IL‐13 production as potential marker to distinguish chromate‐stimulated in vitro response of PBMC derived from allergic/non‐allergic individuals . In 2017, on the other hand, Akerman et al . stated on their experiments with PBMC cultured with/without potassium dichromate that ‘PBMCs from patients with ACD to chromium secreted significantly higher amounts of all cytokines tested, except IL‐4’.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Martins and Reis reported on in vitro IL‐13 production as potential marker to distinguish chromate‐stimulated in vitro response of PBMC derived from allergic/non‐allergic individuals . In 2017, on the other hand, Akerman et al . stated on their experiments with PBMC cultured with/without potassium dichromate that ‘PBMCs from patients with ACD to chromium secreted significantly higher amounts of all cytokines tested, except IL‐4’.…”
Section: Introductionmentioning
confidence: 99%
“…The cytokines investigated herein represent signature cytokines from different Th populations: IFN-γ for Th1; IL-5, IL-13, and IL-31 for Th2; IL-17A for Th17; IL-22 for Th22. IL-2 and IL-3 that are more general markers of Th activation were also measured, as was IL-6, shown to be secreted by potassium dichromate-stimulated PBMC from allergic subjects [ 26 ]. Using ELISpot, production of the Th2 cytokines IL-4 and IL-13 by Ni-stimulated PBMC from the same allergic subjects as in this study was previously shown to be strongly correlated with patch test reactivity [ 23 ].…”
Section: Discussionmentioning
confidence: 99%